Charles Wesley and the struggle for Methodist identity - Lloyd, Gareth, 1962-; Oxford eBooks (Oxford : Oxford University Press, 2007)
This is an appraisal of the life and ministry of the Anglican minister and Evangelical leader Charles Welsey, and his contribution to the early Methodist movement. Lloyd's study offers a new perspective on the formative years of a denomination that today has about 80 million members.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wesley, Charles, -- 1707-1788.; Methodist Church (Great Britain) -- Clergy -- Biography; Electronic books